SILVER-RUSSELL SYNDROME IN COMBINATION WITH INFANTILE CEREBRAL PALSY: CLINICAL OBSERVATION - Коновалова, Нина Геннадьевна; Жарская, Оксана Евгеньевна; Загородникова, Ольга Александровна; Полукарова, Елена Алексеевна (Medicine in Kuzbass, 2025)
A case of combination a rare genetic pathology – Silver-Russell syndrome – with cerebral palsy in three-year-old child is described. The cause of this syndrome is loss of chromosome’s 11p15 (11p15LOM) methylation, maternal uni-parental disomy of chromosome 7, or the presence of monogenic pathogenic variants in imprinted (CDKN1C and IGF2) and non-imprinted (PLAG1 and HMGA2) genes. Clinical manifestations of this syndrome includes dwarfism, multiple stigmas of dysmorphogenesis, skeletal developmental abnormalities, and visceral pathology. Polymorphism of clinical manifestations is due to its connection with various chromosomal, genetic mutations and the influence of various epigenetic factors. The dynamics of the physical and neurological status, the results of clinical and laboratory-instrumental examination of the child with cerebral palsy, Silver-Russell syndrome from birth to 3 years is presented.